The orbital periods of subdwarf B binaries produced by the first stable Roche overflow channel - Chen, X; Han, Z; Deca, J; Podsiadlowski, P (2013)
Long-orbital-period subdwarf B (sdB) stars with main-sequence companions are believed to be the product of stable Roche Lobe overflow (RLOF), a scenario challenged by recent observations. Here we represent the results of a systematic study of the orbital-period distribution of sdB binaries in this channel using detailed binary evolution calculations. We show that the observed orbital-period distribution of long-period sdB binaries can be well explained by this scenario. Furthermore, we find that, if the progenitors of the sdB stars have initial masses below the helium flash mass, the sdB binaries produced from stable RLOF follow a unique mass -- orbital period relation for a given metallicity $Z$; increasing the orbital period from $\sim 400$ to $\sim 1100$\,d corresponds to increasing the mass of the sdB star from $\sim 0.40$ to $\sim 0.49\,M_\odot$ for $Z=0.02$. We suggest that the longest sdB binaries (with orbital period $> 1100$\,d) could be the result of atmospheric RLOF. The mass -- orbital period relation can be tested observationally if the mass of the sdB star can be determined precisely, e.g.\ from asteroseismology. Using this relation, we revise the orbital period distribution of sdB binaries produced by the first stable RLOF channel for the best fitting model of Han et al (2003), and show that the orbital period has a peak around 830\,d.